Functionalized antimicrobial nanofibers: design criteria and recent advances - Hamdan, Nazirah; Yamin, Alisa; Wan Abdul Khodir, Wan Khartini; Abd Hamid, Shafida; Guarino, Vincenzo (MDPI, 2021)
The rise of antibiotic resistance has become a major threat to human health and it is spreading globally. It can cause common infectious diseases to be difficult to treat and leads to higher medical costs and increased mortality. Hence, multifunctional polymeric nanofibers with distinctive structures and unique physiochemical properties have emerged as a neo‐tool to target biofilm and overcome deadly bacterial infections. This review emphasizes electrospun nanofibers’ design criteria and properties that can be utilized to enhance their therapeutic activity for antimi‐ crobial therapy. Also, we present recent progress in designing the surface functionalization of an‐ timicrobial nanofibers with non‐antibiotic agents for effective antibacterial therapy. Lastly, we discuss the future trends and remaining challenges for polymeric nanofibers.